Training Up and Down Stairs for 50 Meter Freestyle Swimming Speed at Win's Swimming Course Swimming Club - Hufadz, Muhamad Ihsan; Shodiq, Burhaan; Aryatama, Bagus (JUMORA: Jurnal Moderasi Olahraga, 2025)
This study examines the effect of stair climbing exercises on the 50-meter freestyle swimming speed of athletes from Win's Swimming Club. The research aims to determine whether incorporating stair climbing exercises as a dryland training method can significantly enhance swimming performance by improving leg strength and cardiovascular endurance. This study employs an experimental research design, involving a sample of 20 swimmers divided into an experimental group and a control group. The experimental group participated in a six-week stair climbing training program in addition to their regular swimming routines, while the control group continued with their standard training program. Swimming speed data was collected before and after the intervention and analyzed using statistical methods. The results indicate that stair climbing exercises contribute to an improvement in freestyle swimming speed in the experimental group compared to the control group. These findings suggest that stair climbing exercises can serve as an effective supplementary training method for competitive swimmers. Further research is recommended to explore the long-term effects and optimal parameters of stair climbing exercises on different swimming styles